Catalytic Performance of NiO/Eggshell Prepared via Sol-Gel Technique in Pyrolysis of Mixed HDPE and PET - Mohamad Dzol, Muhammad Amir Aqil; Balasundram, Vekes; Ibrahim, Norazana; Isha, Ruzinah; Hoang Pham, Le Kim (International Journal of Integrated Engineering, 2026)
This study investigates the catalytic pyrolysis of mixed high-density polyethylene (HDPE) and polyethylene terephthalate (PET) plastic waste utilizing nickel oxide (NiO) loaded on chicken eggshells as catalysts. The research aimed to evaluate the efficiency of various catalysts, including calcium oxides, eggshells, nickel oxides and a series of nickel oxides loaded eggshell catalysts (NC1 to NC5), in producing liquid hydrocarbons from pyrolysis of HDPE and PET. The NC1 to NC5 catalysts were prepared via sol-gel technique and characterized for phase analysis, textural properties, surface morphology, and acidity. The study found that NC1 (5% of NiO and 95% of eggshell) achieved the highest pyrolysis oil yield of 58.01%, outpacing the non-catalytic HDPE-PET process and showcasing the extensive production of valuable hydrocarbons, especially in the C10-C13 (28.74%) and C14-C17 (26.23%) ranges. Additionally, NC1 and eggshell demonstrated superior catalytic efficiency, enhancing both the yield and quality of pyrolysis oil by increasing liquid hydrocarbon concentration and minimizing undesirable components like acids and furans. The findings underscore the potential of using nickel oxide-loaded chicken eggshells as an effective catalyst in sustainable plastic waste management through catalytic pyrolysis, offering a pathway to recover valuable hydrocarbons while addressing environmental challenges associated with plastic waste accumulation.